Fraction Dominoes as Teaching Tools Using Sets in Mathematics Teaching - Muna, Trimurtini, Nur Aizatun (Elementary School Teacher, 2018)
The objectives of this study were to develop a design, to determine the appropriateness and effectiveness of fractional dominoes with set approach. This type of study was Sugiyono's Research and Development (R&D). One set of game consisted of three game devices. The game card had 2 parts; fractions and sets. The material expert assessment result was 96% and the media expert was 94% (very feasible). Furthermore, the learning outcomes showed that learning completeness reached 75%. The media produced an average difference (t-test) in the product test that was 6.1, input test was 10.64 and the learning outcomes enhancement (n-gain) in the product test was 0.8, input test was 0.76 (high). Thus, it could be concluded that the fractional dominoes game as a media with compilation approach on equivalent fraction in Mathematics subject matter of fourth-grade students was effective and feasible to use.